2013
DOI: 10.1080/15226514.2012.723063
|View full text |Cite
|
Sign up to set email alerts
|

Native Australian Species are Effective in Extracting Multiple Heavy Metals from Biosolids

Abstract: Selecting native plant species with characteristics suitable for extraction of heavy metals may have multiple advantages over non-native plants. Six Australian perennial woody plant species and one willow were grown in a pot trial in heavy metal-contaminated biosolids and a potting mix. The plants were harvested after fourteen months and above-ground parts were analysed for heavy metal concentrations and total metal contents. All native species were capable of growing in biosolids and extracted heavy metals to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…Metal accumulating plants with high biomass production and moderate metal uptake can extract more metals than plants with higher metal uptake and less biomass production (Mok et al, 2013). Previous trials at the study site demonstrated that annually harvested willow plantations had the highest annual biomass production in year 3 however this was not observed in this trial.…”
Section: Discussionmentioning
confidence: 58%
“…Metal accumulating plants with high biomass production and moderate metal uptake can extract more metals than plants with higher metal uptake and less biomass production (Mok et al, 2013). Previous trials at the study site demonstrated that annually harvested willow plantations had the highest annual biomass production in year 3 however this was not observed in this trial.…”
Section: Discussionmentioning
confidence: 58%
“…Most biosolids contain elevated concentrations of heavy metals (McBride et al, 1999) and organic contaminants, including polychlorinated biphenyls (PCBs), dioxins, polyaromatic hydrocarbons Ogilvie, 1998), (Sanchez-Monedero et al, 2004), (Rouch et al, 2011), Aerobic sludge 7.6-8.2 2.2 (1.7) 74 (8.5) 101 n/g 2.3 208 526 (Ogilvie, 1998), (Magesan and Wang, 2003), (Rigby and Smith, 2013) Anaerobic sludge 5.8-8.1 4 14 n/g n/g 1.7 (0.2) 520 100 (Ogilvie, 1998), (Magesan and Wang, 2003), (Civeira and Lavado, 2008), (Rigby and Smith, 2013) Digested dry sludge 6.4-7.3 5.5 (0.4) 53 (9.5) 39 n/g 94 4732 431 (Ogilvie, 1998), (Rouch et al, 2011), (Correa et al, 2006) Aged biosolids (>3 yr) 4.4-4.5 2.4 (0.8) n/g n/g n/g 65 208 1848 (Ogilvie, 1998), (Nash et al, 2011), (Mok et al, 2013), (Laidlaw et al, 2012) Aged biosolids (>20 yr) 4.5 n/d 51.6 16.7 (0.7) 107 (2.3) 51 (2.2) 130 (7.3) 1352 (2.5) (Paramashivam et al, 2016b) † EC, electrical conductivity. ‡ CEC, cation exchange capacity.…”
Section: Problems Associated With Land Applicationmentioning
confidence: 99%
“…Over 400 plants, including some edibles, have metal hyperaccumulation abilities, some specific to one metal and others adapted for more general metal accumulation (Prasad and Freitas 2003), while other plant species exclude metals as their metal adaptation strategy (Baker 1981). The bioavailability of metals is influenced by a Table 1 Percentage self-reliance in fresh vegetables, fresh fruit, shell eggs, poultry, and total food and beverage in Cleveland, Ohio, under three different scenarios and using three vegetable production practices: conventional, intensive, and hydroponic (Grewal and Grewal 2012) number of factors, including soil pH, metal chelators, and the percentage available in the soluble or exchangeable fraction (Lai and Chen 2004;Munn et al 2008;PeraltaVidea et al 2009;Mok et al 2013). There is much peerreviewed literature on metal phytoextraction, including extensive reviews of the biochemical mechanisms for metal uptake by plants (Lasat 2002;Pilon-Smits 2005), the possible transfers up the food chain (Peralta-Videa et al 2009), and the diversity of metal-hyperaccumulating plants (Prasad and Freitas 2003).…”
Section: Chemical Contamination Risksmentioning
confidence: 99%